Psychiatric Morbidity and Quality of Life Among Rescued Victims of Human Trafficking in North Karnataka: A Cross-Sectional Study - Anusha M S; Mukul Chamoli; Sagarika S; Sameer Belvi Mangalwedhe; Ashna P (International Journal of Science and Healthcare Research, 2026)
Background: Human trafficking is a major public health and human rights concern associated with severe psychological trauma and poor quality of life. Survivors are vulnerable to psychiatric disorders due to prolonged physical, emotional, and sexual abuse. Data on psychiatric morbidity and quality of life among rescued victims in North Karnataka remain limited. Aim and Objectives: To assess the prevalence of psychiatric morbidity, and evaluate the quality of life among rescued victims of human trafficking residing in a state-run shelter home in North Karnataka. Materials and Methods: This was a descriptive cross-sectional study conducted among 40 rescued victims of human trafficking residing at the state-run shelter home. Psychiatric morbidity was assessed using the Mini International Neuropsychiatric Interview (MINI PLUS Version 7). Depression and anxiety severity were assessed using the Hamilton Depression Rating Scale (HAM-D) and Hamilton Anxiety Rating Scale (HAM-A), respectively. Quality of life was evaluated across physical, psychological, social, and environmental domains. Results: Psychiatric morbidity was identified in 82.5% of participants. Depression and absence of psychiatric illness were observed in 17.5% each, followed by anxiety disorder, post-traumatic stress disorder, and substance use disorder (12.5% each). Schizophrenia and bipolar disorder were present in 10.0% and 7.5% of participants respectively. Mild and moderate depression were observed in 57.1% and 42.9% of participants, respectively. Mild-to-moderate anxiety was present in 57.1% of participants. The quality-of-life scores were highest in the environmental domain (60.3 ± 12.01) and lowest in the psychological domain (50.2 ± 14.10). Conclusion: Psychiatric morbidity is highly prevalent among rescued victims of human trafficking. Quality of life was considerably compromised, with the psychological domain being the most adversely affected. This study emphasized the need for comprehensive mental health and psychosocial rehabilitation services. Keywords: Human trafficking, Psychiatric morbidity, Quality of life, Depression, Anxiety